2020
DOI: 10.1186/s12951-020-00694-3
|View full text |Cite
|
Sign up to set email alerts
|

pH-responsive and hyaluronic acid-functionalized metal–organic frameworks for therapy of osteoarthritis

Abstract: Drug therapy of osteoarthritis (OA) is limited by the short retention and lacking of stimulus-responsiveness after intra-articular (IA) injection. The weak acid microenvironment in joint provides a potential trigger for controlled drug release systems in the treatment of OA. Herein, we developed an pH-responsive metal − organic frameworks (MOFs) system modified by hyaluronic acid (HA) and loaded with an anti-inflammatory protocatechuic acid (PCA), designated as MOF@HA@PCA, for the therapy of OA. Results demons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 61 publications
0
53
0
Order By: Relevance
“…Recently, metal–organic frameworks (MOFs), which composed of metal nodes and organic linkers, have emerged as promising materials for biomedical applications, such as drug delivery [ 26 , 27 ], catalysis [ 28 ], molecular imaging [ 29 ], and biosensing [ 30 ], due to their exceptional large surface area and tunable inner cavity. Among them, zeolitic imidazolate framework-8 (ZIF-8) with low-toxic Zn 2+ and 2-methylimidazole (2-MIN) as the basic units, was recognized as a biocompatible and acid-responsive drug carrier [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, metal–organic frameworks (MOFs), which composed of metal nodes and organic linkers, have emerged as promising materials for biomedical applications, such as drug delivery [ 26 , 27 ], catalysis [ 28 ], molecular imaging [ 29 ], and biosensing [ 30 ], due to their exceptional large surface area and tunable inner cavity. Among them, zeolitic imidazolate framework-8 (ZIF-8) with low-toxic Zn 2+ and 2-methylimidazole (2-MIN) as the basic units, was recognized as a biocompatible and acid-responsive drug carrier [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that ROS lead to chondrocyte apoptosis and cartilage degeneration which accelerate OA progression [33][34][35]. SPD could act as free radical scavengers, but it would be rapidly cleared from the joint cavity [13,36].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from tumor regions, HA coating could target inflammation sites and also improve the water stability of MOFs. Significantly, HA on the surface of MOFs also alleviates inflammation by reducing the expression of cytokines (Xiong et al, 2020).…”
Section: Hyaluronic Acid-mediated Targetingmentioning
confidence: 99%
“…As for microenvironment and pathogenesis, Xiong et al engineered an intelligent pH-responsive drug delivery system modified by hydrophilic agent HA, which could improve the hydrophilicity of MOFs and inflammation of OA simultaneously. In the weak acidic environment of osteoarthritis (OA), MIL-100(Fe) was disrupted, and protocatechuic acid (PCA) was released for alleviating inflammation by reducing the inflammatory mediators (Xiong et al, 2020). Similarly, as mentioned above, an oxidation-responsive MOF, Ce-MOF@ PSS, was designed based on the microenvironment of inflammatory bowel disease (IBD) and antioxidant ability of Ce 3+ /Ce 4+ .…”
Section: Inflammatory Diseasesmentioning
confidence: 99%